Caregiving for People With Dementia or Cognitive Impairment During the COVID-19 Pandemic: A Review. (October 2022) - Chyu, Joanna; Cantu, Philip; Mehta, Neil; Markides, Kyriakos
The COVID-19 pandemic has been a major source of stress for informal caregivers for people with dementia. Studies show the unique challenges caregivers face, such as social isolation, extended work hours, and adherence to public health guidelines. We conducted a narrative review of factors impacting well-being of informal caregivers of older adults with dementia during the COVID-19 pandemic. Sixty-four papers were identified as published between June 2020 and December 2021. All studies were conducted in the U.S. or other Western countries and were cross-sectional and conducted prior to COVID-19 vaccines. Articles highlighted increasing burdens such as financial and physical stress, as well as worsened psychological well-being from anxiety and depression. Protective factors such as social support and telehealth interventions also emerged. Limitations include lack of longitudinal information to identify broader themes on caregiving during the pandemic. Studies not only identified new, pandemic-related risk factors, but also a heightened effect of pre-existing risk factors (e.g., income, living situation) on caregiver burden.